Prevalence of Cardiovascular Disorders in Iranian Patients Suffering from Obstructive Sleep Apnea - Gholamreza Shirani; Seyyedeh Pouya Morovati; Ahmad Reza Shamshiri; Mehdi Nouri; Narges Ezzati Givi; Mohammad Farhadi (Tehran University of Medical Sciences, 2016)
Objectives: Obstructive sleep apnea (OSA) can lead to various cardiovascular disorders (CVD) such as hypertension. There is no documented data about this relationship among the Iranian population. The aim of this study was to obtain comprehensive information about the severity of OSA as a cause of CVD and its relationship with other important risk factors. Materials and Methods: In this cross sectional study, we studied patients with OSA and apnea/hypopnea index of 5 or more. The data were collected from the patients' polysomnography report and medical files. Data analysis was done with SPSS version 18. Results: The majority of patients were males (71.9%). Among the studied individuals, 26.5% showed at least one sign of CVD, and hypertension was the most common condition (74.5%). Multiple regression analysis showed that the odds ratios for one unit increase in BMI and one year increase in age were 1.13 and 1.12, respectively (P<0.001).  Conclusions: In our study, BMI and age had the strongest relationship with CVD. Thus, public health care providers should implement weight control strategies and improve diagnostic and treatment procedures for the elderly patients.